Historic Distribution of Mountain Quail in the Pacific Northwest - John A. Crawford (National Quail Symposium Proceedings, 2017)
Mountain quail (Oreortyx pictus) are among the least studied of the North American quails. The prehistoric and early historic distributions of this bird are uncertain. In the Pacific Northwest, mountain quail were first recorded by Lewis and Clark in 1806 near the Columbia River adjacent to the Cascade Range in Oregon. Written evidence relating to the original distribution of mountain quail in this area indicated that the birds were found from the Oregon Coast Range to the Cascades along the Columbia River and southward. Translocations of birds into this region began in 1860 and continued for several decades, which further confused the historic status. Eventually, mountain quail were distributed from southern British Columbia throughout Washington and into western Idaho and eastern Oregon by the early 20th century. Archeological evidence revealed it is possible that mountain quail existed in west-central Idaho, likely as refugia populations, 700 to 1000 years ago. Populations in Idaho and the interior Columbia River Basin have declined substantially during the past several decades. Similar declines have not been observed in the Pacific Northwest (western Oregon) or in the humid coastal region of western California.